Fluctuating Asymmetry Increases with Heat Stress Disruptions on Bali Cattle (Bos javanicus) at Different Altitude - Ikhsan Suhendro; Jakaria Jakaria; Rudy Priyanto; Wasmen Manalu; Ronny Rachman Noor (Indonesian Center for Animal Research and Development (ICARD), 2021)
Bali cattle (Bos javanicus) are common species distributed throughout Indonesia to survive in tropical hot, and humid climates. Fluctuating asymmetry (FA) is a random deviation from perfect bilateral symmetry. FA is often used to measure developmental stability in individuals and can be used as a marker for the impact of environmental and genetic stress. This study aims to investigate the pattern of developmental instability in Bali cattle as caused by environmental stress at various altitudes using the FA index. FA indexes in this study were used to compare asymmetrical physical traits of Bali cattle in Sembalun high altitude and Serading low altitude. Sixty-five Bali cattle were used in this study reared at different altitudes, namely Serading, Sumbawa Island (50 m above sea level), and Sembalun, Lombok Island (1,186 m above sea level). The physical traits of Bali cattle measured were horn circumference (horn), a distance of hip to spine bone (pelvic), metatarsal circumference (metatarsal), and metacarpal circumference (metacarpal). The FA1 and FA5 indexes showed significant metacarpal differences between Bali cattle reared at Sembalun and Serading population (P<0.05). FA11 multiple trait index as a composite of all traits revealed a significant difference as well. (P<001). It can be concluded that various heat stress by altitude impacts the asymmetry of Bali cattle.